Glycopeptide vaccine on DNA-histone carrier and its impact on ζ-potential of effector cells during experimental treatment of lymphoblastic leukemia - Janisch, Yu.V.; Artamonova, A.B.; Shlyakhovenko, V.A. (Experimental Oncology, 2013)
Aim: To increase the effectiveness of anticancer vaccine delivery and activity via its immobilization on reconstructed chromatin (RC). Materials and Methods: The hybrid mice of CDF-1 line with transplanted P-388 leukemia were used. Reconstructed chromatin was obtained from the thymus of inbred rats. Glycopeptide cancer vaccine prepared from P-388 leukemia cells, was immobilized of RC. ζ-potential of thymocytes from tumor-bearing mice was calculated from Smoluchowski equation. Results: The data have demonstrated the principal possibility of using the fragments of reconstructed chromatin of heterologous origin as a carrier of glycopeptide cancer vaccine prepared from the cells of P-388 leukemia. Preventive immunization with the correspondingly immobilized vaccine normalized ζ-potential of thymocytes in animals with transplanted P‑388 leukemia. Conclusions: The use of immobilization of glycopeptide cancer vaccine on reconstructed chromatin improves anticancer activity of the vaccination.